2017
DOI: 10.1002/2017gb005657
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Composition of Natural Nanoparticles and Fine Colloids in European Forest Stream Waters and Their Role as Phosphorus Carriers

Abstract: Biogeochemical cycling of elements largely occurs in dissolved state, but many elements may also be bound to natural nanoparticles (NNP, 1–100 nm) and fine colloids (100–450 nm). We examined the hypothesis that the size and composition of stream water NNP and colloids vary systematically across Europe. To test this hypothesis, 96 stream water samples were simultaneously collected in 26 forested headwater catchments along two transects across Europe. Three size fractions (~1–20 nm, >20–60 nm, and >60 nm) of NNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 56 publications
(76 reference statements)
0
38
1
Order By: Relevance
“…This was attributed to the greater contents of Fe and Al in acidic soil than in alkaline soil, and that the presence of Al and Fe oxides may have enhanced the adsorption of P and stabilization of soil aggregates [15,31,63]. Al and Fe oxides have been recognized as important carriers of P coll [64][65][66][67].…”
Section: Colloidal P Content In Aggregatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to the greater contents of Fe and Al in acidic soil than in alkaline soil, and that the presence of Al and Fe oxides may have enhanced the adsorption of P and stabilization of soil aggregates [15,31,63]. Al and Fe oxides have been recognized as important carriers of P coll [64][65][66][67].…”
Section: Colloidal P Content In Aggregatesmentioning
confidence: 99%
“…We observed that the CR value of (silt + clay)-sized particles was larger than that of aggregates of other sizes, while the CR of large macroaggregates was the lowest in most soils, indicating that the (silt + clay)sized particles contribute more to the P coll loss potential, while macroaggregates immobilized soil P coll . Colloidal P is highly bound to Fe and Al on the surface of macroaggregates [15,68], enabling the formation of a stable composite structure that can resist the shear force of pore flow [64,65]. Similarly, soil macroaggregates can increase the adsorption of P coll on the surface and reduce its mobility [26].…”
Section: Loss Potential Of Colloidal P In Aggregatesmentioning
confidence: 99%
“…Locating and apportionment of the sources and fluxes of the dissolved vs. collodial P conveyed by rivers in landscapes remains a longstanding and fundamental challenge for catchment scientists (see McClain et al, 2003;Bol et al, 2016;Gottselig et al, 2017b;Missong et al, 2018), with major implications for land management and nutrient pollution mitigation strategies. Colloidal P is characterized as dissolved P in most routine water quality monitoring programs (Gottselig et al, 2017a), however, it is believed to have reduced bioavailability compared to the truly dissolved P (Baken et al, 2014).…”
Section: Difficulties In Predictions Of Dissolved/colloidal/particulamentioning
confidence: 99%
“…In comparison, the origin of the finest inorganic colloidal fraction transported by rivers remains far less constrained and understood. This question is of particular importance because colloidal nanoparticles have a substantial surface area, and typically serve as sinks and/or sources for trace metals, nutrients and pollutants in the natural environment (e.g., Hill and Aplin, 2001;Pokrovsky and Schott, 2002;Kulaksiz and Bau, 2013;Trostle et al, 2016;Gottselig et al, 2017).…”
Section: Introductionmentioning
confidence: 99%